The Role Of The Agricultural Department Of Kutaisi Military Governor In The Development Of Batumi Agriculture (1878-1900) - Gogolishvili, Otar (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2018)
In the state archives of Adjaria, there is one document regarding the order of the state border and land issued by the military governor of Kutaisi in 1879 which is about the restoration of the borders of Russia and Turkey, focusing the location of the villages Tsekhedana and Natskhavatevi. According to this document, it becomes clear that Natskhavatevi had never been under Turkish control, it was among the borders of Guria and Adjara. Tsekhedana was a Christian village, as for Natskhavatevi, its population was Muslim. On July 1, 1879 after uniting Batumi region to Russia, Polcovnic Frier made a report for the Caucasus army leader regarding launching the rule of land possession, according to which the possession rights on the lands would be restricted for the locals. Later, on July 11, 1880 Kutaisi military governor held a meeting in Kutaisi participated by the Batumi military governor. They discussed the plans of Freier and Pavle Stefanov, Kutaisi agricultor. Russian rule of agriculture acting in Batumi was adapted to the agriculture law issued in Russia in 1861. Before the reunion of Batumi in 1878 Turkish law of land ownership was acting which used to give high priority to religious servants. Russian was trying to decrease the influence of religious servants by issuing land ownership law.